Filtration of Submicron Soot Particles, Oil Droplets, and their Mixtures on Single- and Multi-layer Fibrous Filters - Mateusz Kamiński; Jakub M. Gac; Piotr Sobiech; Paweł Kozikowski; Szymon Jakubiak; Tomasz Jankowski (Aerosol and Air Quality Research)
Abstract The dynamics of filtration efficiency and pressure drop during the simultaneous filtration of soot and oil aerosols on single- and multi-layer filters were investigated, and the determined filtration efficiency was compared with the theoretical efficiency obtained via the classical filtration theory. Additionally, the influence of liquid-phase aerosols on the morphology of the formed deposits was investigated. It was concluded that the addition of oil aerosols decreased the filtration efficiency and lowered the pressure drop increase rate for multi-layer filters. Additionally, for the filtration of aerosols containing soot and high oil concentrations, once maximum filtration efficiency was reached, an efficiency decrease occurred. The system imperfection factor was proposed as a mean to predict the efficiency of multi-layer filters. The modified version of the single fibre efficiency method was used to calculate filter mass change with reasonable accuracy.